Structural Investigation of SBGESE Glasses by High Resolution X-Ray Photoelectron Spectroscopy - R. Golovchak; A. Kovalski; R.M. Mehra; L.P. Purohit; D.C. Sati; H. Jain (Журнал нано- та електронної фізики)
The evolution of the structure of Sb8Ge32Se60 (Z=2.72) and Sb20Ge20Se60 (Z=2.60) chalcogenide glasses is determined by high resolution X-ray photoelectron spectroscopy. Glasses with Z=2.60 the structure consists of deformed tetrahedra and pyramids, in which at least one Se atom is substituted by Ge or Sb atom. For the Z=2.72 structure consisting of shared pyramids and tetrahedra with two or more Se atoms substituted by the cations. At the same time, Se-Se dimers are present in both compositions.